Screening of Penicillium Species and Optimisation of Culture Conditions for the Production of Ergot Alkaloids Using Surface Culture Fermentation Process: Ergot Alkaloids from Penicillium Species (Biological Sciences - PJSIR, 2015)
The present study deals with the screening of fungal species and suitable fermentation medium for the production of ergot alkaloids. Various species of genus Penicillium were grown on differentfermentation media by employing surface culture fermentation technique to achieve the most suitable medium and the best Penicillium sp. The results showed that medium M5 gave maximum yield withPenicillium commune. Different culture conditions such as effect of different carbon and nitrogen sources, their concentration levels, different pH values and sizes of inoculum on the production of ergot alkaloids were also studied to improve the yield. Maximum production of ergot alkaloids (4.32 mg/L) was achieved with 15 mL spore suspension at pH 5 in fermentation medium containing 35% (w/v) sucrose. All these  results indicate that culture conditions are very much crucial to improve the yield of ergot alkaloids produced by Penicillium commune through surface culture process.